The relationship between motives of entrepreneurial behavior and venture maturity - Bobera, Dušan; Leković, Bojan; Berber, Nemanja (Industrija, 2017)
Countries at a different level of development exhibit a variety of entrepreneurial initiatives and activities in terms of motives of entrepreneurial behavior, but also the scope and structure of entrepreneurial ventures. The aim of this paper is to explore the relationship between the degree of economic development and the motives of entrepreneurial behavior. In order to perform a more detailed overview of the research subject, the research area expands on the scope and structure of entrepreneurial activity, with the aim of identifying the impact of the motives of entrepreneurial behavior on the entrepreneurial process observed in its phases. Characteristics of selected variables and the size of the research sample conditioned the usage of the Spearman’s correlation coefficient and the Chi-square test. The results indicate a positive correlation between the level of economic development and opportunity motive of entrepreneurial ventures. This motive is also found to be a generator of maturity of entrepreneurial ventures. More specifically, the higher percentage of participation of the entrepreneurial ventures with opportunity motive is associated with a higher percentage of enterprise in more mature stages, which is especially reflected in the group of highly developed countries.